Timing of Antihypertensive Medications on Key Outcomes in Hemodialysis: A Cluster Randomized Trial. Issue 11 (25th November 2021) - Chang, Tara I.; Tatoian, Emily Tamar; Montez-Rath, Maria E.; Chertow, Glenn M.
Visual Abstract: Abstract : Key Points: Taking BP medications before hemodialysis was not noninferior to holding BP medications for the outcome of intradialytic hypotension. Taking BP medications before hemodialysis (rather than holding) reduced the occurrence of uncontrolled hypertension. Whether any benefit of holding BP medications on IDH is offset by potential harms related to higher predialysis BP remains to be seen. Background: We conducted this study to examine the effect of taking versus holding BP medications before hemodialysis on intradialytic hypotension (IDH). Methods: In this cluster randomized trial, each dialysis unit was randomly designated as TAKE or HOLD units. Participants within a TAKE unit were instructed to take all BP medications as prescribed, whereas participants within a HOLD unit were instructed to hold medications dosed more than once daily before hemodialysis. The intervention lasted for 4 weeks. We hypothesized that TAKE would be noninferior to HOLD on the primary outcome of asymptomatic IDH, defined as ≥30% of sessions with nadir systolic BP <90 mm Hg and on the following secondary outcomes: uncontrolled hypertension (predialysis systolic BP >160 mm Hg), failure to achieve dry weight, and shortened dialysis sessions. Results: We randomized 10 dialysis units in a 1:1 ratio to TAKE or HOLD, which included 65 participants in TAKE and 66 participants in HOLD. We did not show that TAKE was noninferior to HOLD for the primary IDH outcome (mean unadjusted difference of 8%; 95% CI, −3% to 19%). TAKE was superior to HOLD for the outcome of uncontrolled hypertension (mean unadjusted difference of −15%, 95% CI, −28% to −1%). TAKE was noninferior to HOLD for the outcomes of failure to achieve dry weight and shortened dialysis sessions. Conclusions: In this cluster randomized trial that randomized patients to either taking or holding BP medications before hemodialysis, a strategy of taking BP medications dosed more than once daily was not noninferior to holding BP medications for the primary outcome of IDH, but did reduce the occurrence of uncontrolled hypertension. Whether any potential benefit of holding BP medications on reducing IDH is offset by any potential harm related to higher predialysis BP remains to be seen.